“TAG” TEMAN DAN #HASTAG REKONSEPSI INTERAKSI SOSIAL DI PLATFORM INSTAGRAM - Mita Rosaliza; Raja Syamsidar; Hesti Asriwandari (Jurnal Ilmu Budaya, 2022)
Tag a friend in the comments column on the Instagram platform is one mechanism to start interacting between users on social media. Is it possible to just "tag" friends who have there been social interactions intended by sociologists, psychologists,s and communication experts? This article is to explore how social media carries out the process of social interaction, and whether simply tagging a friend on Instagram can be considered a social interaction. The results of the study show that the use of social media is rarely considered a social interaction, after surfing on social media for approximately the first 7-10 minutes, 116 samples of Instagram users showed that social media behavior rarely chatted and commented, on average they only status updating, stalking and also looking for the information. The use of social media and social interaction sometimes occur together, but only 3% of social interactions occur through the Instagram platform. It is said that social interaction through this platform usually focused on having conversations, and exchanging with relatively closer relational relationships. Secondary data analysis and surveys of Instagram users are used in this article to analyze the process of social interaction on the Instagram platform supported by literature studies from several sociologists, psychologists, and also communication experts who argue about social interaction. It can be said, each media is social in a unique way including the Instagram platform, and needs further discussion in conceptualizing the boundaries of social interaction in social media.